Grip Strength and Anthropometric Characteristics among Hispanic Children and Adolescents with Obesity and Insulin Resistance - Diaz-Cotto, Enibeth; Ramirez-Marrero, Farah A.; Leyva-Jordán, Carlos A. (Puerto Rico Health Sciences Journal, 2026)
Objective: The objectives of this study were: 1) to describe and evaluate associations between grip strength, and anthropometric characteristics in pediatric patients with obesity and insulin resistance (IR), and 2) to compare IR using the HOMA-IR model and fasting insulin level. Methods: Secondary data analysis was conducted using results from 41 children and adolescents with obesity and IR (18 boys and 23 girls, mean age: 14.4 ± 3.1 years) enrolled in a clinically supervised weight management program. Independent t-tests were conducted to detect sex differences, and correlation analyses to determine associations between variables. Results: Mean body mass index (BMI) was above the 99th percentile, with 109.6±19.7 cm waist circumference, 45.6±6.7% body fat, 59.9±15.7 kg lean mass, 91.8±8.9 mg/dL fasting glucose, 36.9±31.5 μU/m fasting insulin, 8.6±1.2 HOMA-IR, and 30.2±9.0 kg grip strength. Boys had greater height, fasting glucose, and lean mass compared to girls. There was a significantly high correlation (r=0.98, P<0.0001) between fasting insulin and HOMA-IR. Grip strength was not associated with insulin and HOMA-IR. However, grip strength relative to lean mass inversely correlated with waist circumference, percent body fat, and BMI percentile. Conclusion: Fasting insulin and HOMA-IR do not appear to influence grip strength in the group of children and adolescents with obesity and IR in this study. However, grip strength was significantly influenced by anthropometric characteristics. The use of a fasting insulin cutoff at or above 12 μU/mL appears appropriate to detect insulin resistance in this pediatric group.